Kemampuan Menulis Kata Tulisan Arab Melayu Siswa Kelas 4a SD Negeri 148 Pekanbaru - Monalisa Putri; Rahma Yulia Ningsih; Raja Bani Firmansyah; Hasnah Faizah AR (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2022)
Writing can be said as an activity that forms symbols. But writing is more than producing graphic symbols, just as speaking is defined not only as the production of sound. These symbols must be arranged, according to certain conventions, to form words and words arranged to form sentences. The ability to write is not an ability that can be obtained automatically. The aim of teaching Arabic-Malay writing is to recognize, train, and develop the ability to understand and carry out how to read and write properly and correctly according to Arabic-Malay regulations, as well as express simple ideas or impressions orally and in writing. In conducting this research the authors used a type of quantitative research. In this study the data collection method was carried out by testing the ability to write Malay Arabic words in the questionnaire given. After conducting research on the ability to write Malay Arabic words for students in grade 4a at SD Negeri 148 Pekanbaru, it was found that the students in grade 4a at SD Negeri 148 Pekanbaru as a whole had the ability to write Malay Arabic words in the low category with a percentage of 18.62%. In two-syllable Malay Arabic words, students in grade 4a SD Negeri 148 have a low ability category with a percentage of 7.93% and for Malay Arabic words with more than two syllables are also in the low category with a percentage of 19.31%. This proves that students do not understand how to write Arabic Malay words in two or more syllables.